Personal determinants of vandal behaviour among urban school and student youth from a gender perspective - O. V. Kruzhkova; I. V. Deviatovskaia; M. S. Krivoshchekova (Russian State Vocational Pedagogical University, 2021)
Introduction. Vandalism is an urgent modern problem. This problem is especially acute for modern megalopolises, the environment of which is often a subject for damages and unauthorised changes. However, the megalopolis, possessing specific environmental characteristics, in a sense creates favourable conditions for vandalism through anonymisation, a decrease in social control, the adoption of borderline deviant-like forms of behaviour, etc. At the same time, foreign and Russian researchers refer to adolescents and young adult males as the subjects of vandal activity, i.e. those young people, who are mostly the subjects of education (schoolchildren, students). Their destructive vandal activity can spread in the space of an educational organisation or in the urban territory. Most often, males are at risk of vandalism, but there are examples of female vandalism. In such a case, the question of the personal determination of vandal behaviour of schoolchildren and students as active subjects transforming the environment remains open.The aim of the present research was to identify personality characteristics as facilitating and inhibiting predictors of motivational readiness for vandal behaviour of school and university students in a modern Russian megalopolis taking into account the gender factor.Research methodology, methods and techniques. The research was carried out among students of schools and universities in Ekaterinburg (an urban area with all the features of a modern Russian megalopolis). The study involved 132 people from 13 to 24 years (42 males, 90 females; 57 schoolchildren, 75 students). The HEXACO Personality Inventory, Dark Triad Personality Test and the questionnaire "Motives of Vandalism" were used as diagnostic tools. Mathematical and statistical processing of the results was carried out using comparative statistics (Student's t-test) and linear regression analysis.The results of the study confirm the existence of significant differences in the motivational readiness for vandalism among the male and female subsamples. The constructed gender-differentiated regression models made it possible to identify a number of significant personality predictors of vandal behaviour. Predictors-facilitators include personality traits such as psychopathy and narcissism. The predictors-inhibitors of vandalism are honesty-modesty, extraversion, altruism, conscientiousness (female subsample), openness to new experience, Machiavellianism.The scientific novelty is in the fact that specific for the Russian sample of students and schoolchildren living in a megalopolis, personal factors of vandal behaviour were identified, taking into account gender differentiation.The practical significance is due to the potential possibilities of using the obtained data for preventing vandalism by students in the framework of the educational process in an educational organisation.